2013
DOI: 10.1111/adb.12051
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in working memory deficits during nicotine withdrawal

Abstract: Nicotine withdrawal is associated with subtle working memory deficits that predict subsequent relapse. We examined the neural substrates underlying these processes in treatment-seeking smokers, and explored the moderating influence of age on abstinence-induced alterations in brain activity and performance. Sixty-three smokers participated in two blood-oxygen-level dependent (BOLD) functional magnetic resonance imaging (fMRI) scans while performing a visual N-back task on two separate occasions: smoking as usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 51 publications
(67 reference statements)
1
54
0
Order By: Relevance
“…Critically, dlPFC hypoactivation among smokers likely contributes to working memory deficits, which are predictive of smoking relapse (23, 57-59). The current results provide support for the utility of considering dlPFC activity as a potential interventional target for smoking cessation (23, 60, 61). Conversely, our results indicated that the bilateral parietal cortices, right middle frontal gyrus, and ACC were more likely to show drug-induced activity increases in studies involving nonsmokers.…”
Section: Discussionsupporting
confidence: 62%
“…Critically, dlPFC hypoactivation among smokers likely contributes to working memory deficits, which are predictive of smoking relapse (23, 57-59). The current results provide support for the utility of considering dlPFC activity as a potential interventional target for smoking cessation (23, 60, 61). Conversely, our results indicated that the bilateral parietal cortices, right middle frontal gyrus, and ACC were more likely to show drug-induced activity increases in studies involving nonsmokers.…”
Section: Discussionsupporting
confidence: 62%
“…As noted above, prior work with the visual N-back task by our group (Ashare et al, 2013b;Falcone et al, 2014;Lerman et al, 2014;Loughead et al, 2009Loughead et al, , 2010 and others (Owen et al, 2005;Satterthwaite et al, 2013) has identified three task-active (right DLPFC, left DLPFC, MF/CG) and two task-negative (PCC, vmPFC) regions sensitive to abstinence challenge. ROI masks were functionally defined using the main effect of memory load (controlling for condition) in a whole-brain repeated measures condition (smoking satiety, abstinence challenge) by memory load (N-back level) ANOVA.…”
Section: Roi Definitionmentioning
confidence: 76%
“…In addition to reducing working memory performance (Mendrek et al, 2006;Myers et al, 2008), brief abstinence is associated with reduced working memory-related activation in the dorsolateral prefrontal cortex (DLPFC) and medial frontal/ cingulate gyrus (MF/CG; Falcone et al, 2014;Loughead et al, 2010), decreased working memory-related suppression of activity in regions within the default mode network (posterior cingulate cortex (PCC), ventromedial prefrontal cortex (vmPFC); Beaver et al, 2011;Falcone et al, 2014;Loughead et al, 2010), and dysregulated inter-network functional connectivity during task performance and at rest (Jacobsen et al, 2007;Lerman et al, 2014;Sutherland et al, 2013). FDA-approved medications, such as varenicline and bupropion, can reverse abstinence-induced working memory deficits and related neural activation in studies of abstinent smokers tested during medication vs placebo Perkins et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies have demonstrated that brief abstinence from nicotine alters patterns of brain activation during the performance of effortful cognitive tasks (Froeliger, Modlin, Kozink, Wang, & McClernon, 2012;Kozink, Kollins, & McClernon, 2010;Kozink, Lutz, Rose, Froeliger, & McClernon, 2010;Sweet et al, 2010;Xu et al, 2005;Xu et al, 2006), and that these effects are moderated by age (Falcone et al, 2013), genotype (Loughead et al, 2009), and individual differences in performance (Nichols, Gates, Molenaar, & Wilson, 2013). More recently, fMRI has been used to characterize the mechanisms through which nicotine replacement therapy (Beaver et al, 2011;Cole et al, 2010) and other medications for the treatment of tobacco dependence (e.g., varenicline; Loughead et al, 2010) remediate withdrawal-related cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%